Dispersion Forces Drive the Formation of Uranium-Alkane Adducts - Jung, Julie; Löffler, Sascha; Langmann, Jan; Heinemann, Frank Wilhelm; Bill, Eckhard; Bistoni, Giovanni; Scherer, Wolfgang; Atanasov, Mihail; Meyer, Karsten; Neese, Frank (Journal of the American Chemical Society, 2020)
Single-crystal cryogenic X-ray diffraction at 6 K, electron paramagnetic resonance spectroscopy, and correlated electronic structure calculations are combined to shed light on the nature of the metal-tris(aryloxide) and Î•2-H, C metal-alkane interactions in the [((t·BuArO)3tacn)UIII(Mecy-C6)]·(Mecy-C6) adduct. An analysis of the ligand field experienced by the uranium center using ab initio ligand field theory in combination with the angular overlap model yields rather unusual U-OArO and U-Ntacn bonding parameters for the metal-tris(aryloxide) interaction. These parameters are incompatible with the concept of σ and πmetal-ligand overlap. For that reason, it is deduced that metal-ligand bonding in the [((t·BuArO)3tacn)UIII] moiety is predominantly ionic. The bonding interaction within the [((t·BuArO)3tacn)UIII] moiety is shown to be dispersive in nature and essentially supported by the upper-rim tBu groups of the (t·BuArO)3tacn3- ligand. Our findings indicate that the axial alkane molecule is held in place by the guest-host effect rather than direct metal-alkane ionic or covalent interactions.
CRIS-Team Scopus Importer:2020-02-04

Molecular and Electronic Structure of Linear Uranium Metallocenes Stabilized by Pentabenzyl-Cyclopentadienyl Ligands - Löffler, Sascha; Heinemann, Frank Wilhelm; Carpentier, Ambre; Maron, Laurent; Meyer, Karsten (Organometallics, 2022)
We report a series of uranium complexes stabilized by the pentakis-benzyl-derivatized cyclopentadienyl ligand, Cp-Bn5. Treatment of [UCl4] and [UI3(1,4-dioxane)(1,5)] with 2 equiv of the potassium salt, (CpK)-K-Bn5, yielded the corresponding complexes [(CpBn5)(2)UIV(Cl)(2)] (1) and [(CpBn5)2U(III)(I)] (4). Subsequently, tetravalent 1 is either methylated to give [(Cp-Bn5)(2)U-IV(Me)(2)] (2) or reduced to form trivalent [(CpBn5)(2)U-III(mu-Cl)(2)K(OEt2)(3)] (3). Oxidation of 4 with AgI yields [(CpBn5)(2)U-IV(I)(2)] (5), which was found to generate rarely observed, linear uranium metallocenes [(CpBn5)2U(IV)(NCMe)(5)][X](2) (X = PF6- (6), BPh4- (7)) upon abstraction of the iodide ligands with thallium salts in acetonitrile. All complexes were characterized by H-1 NMR spectroscopy, CHN elemental analysis, UV-vis-NIR spectroscopy, and SQUID magnetization measurements. The solid-state molecular structures of 1-7 were determined by single-crystal X-ray diffraction analysis. An in-depth computational analysis revealed the peculiar electronic structure of the linearly coordinated title complex 7 and its closely related, parent [(Cp*)(2)U-IV(NCMe3)(5)](2+) dication.
CRIS-Team WoS Importer:2022-08-05

Unprecedented pairs of uranium (IV/V) hydroxido and (IV/V/VI) oxido complexes supported by a seven- coordinate cyclen-anchored tris-aryloxide ligand - Löffler, Sascha; Hümmer, Julian; Scheurer, Andreas; Heinemann, Frank Wilhelm; Meyer, Karsten (Chemical Science, 2022)
We present the synthesis and reactivity of a newly developed, cyclen-based tris-aryloxide ligand precursor, ,- namely cyclen(Me)(t-Bu,t-BuArOH)(3), and its coordination chemistry to uranium. The corresponding uranium(III) complex [U-III((OArt-Bu,t-Bu)(3)(Me)cyclen)] (1) was characterized by H-1 NMR analysis, CHN elemental analysis and UV/vis/NIR electronic absorption spectroscopy. Since no single-crystals suitable for X-ray diffraction analysis could be obtained from this precursor, 1 was oxidized with methylene chloride or silver fluoride to yield [(cyclen(Me)(t-Bu,t-BuArOH)(3))U-IV(X)] (X = Cl (2), F (3)), which were unambiguously characterized and successfully crystallized to gain insight into the molecular structure by single-crystal X-ray diffraction analysis (SC-XRD). Further, the activation of H2O and N2O by 1 is presented, resulting in the U(IV) complex [(cyclen(Me)(t-Bu,t-BuArOH)(3)))U-IV(OH)] (4) and the U(V) complex Rcyclen(Me)(t-Bu,t-BuArOH)(3))U-IV(O)] (6). Complexes 2, 3, 4, and 6 were characterized by H-1 NMR analysis, CHN elemental analysis, UV/vis/NIR electronic absorption spectroscopy, IR vibrational spectroscopy, and SQUID magnetization measurements as well as cyclic voltammetry. Furthermore, chemical oxidation of 3, 4, and 6 with AgF or AgSbF6 was achieved leading to complexes Rcyclen(Me)(t-Bu,t-BuArOH)(3))U-V(F)(2)] (5), Rcyclen(Me)(t-Bu,t-BuArOH)(3))U-V(OH)][SbF6] (7), and Rcyclen(Me)(t-Bu,t-BuArOH)(3))U-V(O)][SbF6] (8). Finally, reduction of 7 with KC8 yielded a U(IV) complex, spectroscopically and magnetochemically identified as K [(cyclen(Me)(t-Bu,t-BuArOH)(3))U-IV(O)].
CRIS-Team WoS Importer:2022-09-16

Uranium-Mediated Peroxide Activation and a Precursor toward an Elusive Uranium cis-Dioxo Fleeting Intermediate - Hartline, Douglas; Löffler, Sascha; Fehn, Dominik; Kasper, Joseph M.; Heinemann, Frank Wilhelm; Yang, Ping; Batista, Enrique R.; Meyer, Karsten (Journal of the American Chemical Society, 2023)
The activation of chalcogen-chalcogen bonds using organometallic uranium complexes has been well documented for S-S, Se-Se, and Te-Te bonds. In stark contrast, reports concerning the ability of a uranium complex to activate the O-O bond of an organic peroxide are exceedingly rare. Herein, we describe the peroxide O-O bond cleavage of 9,10-diphenylanthracene-9,10-endoperoxide in nonaqueous media, mediated by a uranium(III) precursor [((Me,AdArO)3N)UIII(dme)] to generate a stable uranium(V) bis-alkoxide complex, namely, [((Me,AdArO)3N)UV(DPAP)]. This reaction proceeds via an isolable, alkoxide-bridged diuranium(IV/IV) species, implying that the oxidative addition occurs in two sequential, single-electron oxidations of the metal center, including rebound of a terminal oxygen radical. This uranium(V) bis-alkoxide can then be reduced with KC8 to form a uranium(IV) complex, which upon exposure to UV light, in solution, releases 9,10-diphenylanthracene to generate a cyclic uranyl trimer through formal two-electron photooxidation. Analysis of the mechanism of this photochemical oxidation via density functional theory (DFT) calculations indicates that the formation of this uranyl trimer occurs through a fleeting uranium cis-dioxo intermediate. At room temperature, this cis-configured dioxo species rapidly isomerizes to a more stable trans configuration through the release of one of the alkoxide ligands from the complex, which then goes on to form the isolated uranyl trimer complex.
CRIS-Team Scopus Importer:2023-05-19